Pharmacological Dissection of the Cellular Mechanisms Associated to the Spontaneous and the Mechanically Stimulated Atp Release by Mesentery Endothelial Cells: Roles of Thrombin and Trpv - Garcia Huidobro-Toro, J; Acuna-Castillo, C; Donoso-Gomien, M (Springer Netherlands, 2018)
Endothelial cells participate in extracellular ATP release elicited by mechanosensors. To characterize the dynamic interactions between mechanical and chemical factors that modulate ATP secretion by the endothelium, we assessed and compared the mechanisms participating in the spontaneous (basal) and mechanically stimulated secretion using primary cultures of rat mesentery endothelial cells. ATP/metabolites were determined in the cell media prior to (basal) and after cell media displacement or a picospritzer buffer puff used as mechanical stimuli. Mechanical stimulation increased extracellular ATP that peaked within 1 min, and decayed to basal values in 10 min. Interruption of the vesicular transport route consistently blocked the spontaneous ATP secretion. Cells maintained in media lacking external Ca2+ elicited a spontaneous rise of extracellular ATP and adenosine, but failed to elicit a further extracellular ATP secretion following mechanical stimulation. 2-APB, a TRPV agonist, increased the spontaneous ATP secretion, but reduced the mechanical stimulation-induced nucleotide release. Pannexin1 or connexin blockers and gadolinium, a Piezo1 blocker, reduced the mechanically induced ATP release without altering spontaneous nucleotide levels. Moreover, thrombin or related agonists increased extracellular ATP secretion elicited by mechanical stimulation, without modifying spontaneous release. In sum, present results allow inferring that the spontaneous, extracellular nucleotide secretion is essentially mediated by ATP containing vesicles, while the mechanically induced secretion occurs essentially by connexin or pannexin1 hemichannel ATP transport, a finding fully supported by results from Panx1−/− rodents. Only the latter component is modulated by thrombin and related receptor agonists, highlighting a novel endothelium-smooth muscle signaling role of this anticoagulant. © 2018, Springer Science+Business Media B.V., part of Springer Nature.